Securities Transaction Tax in France: Impact on market quality and inter-market price coordination - Peter Gomber; Martin Haferkorn; Kai Zimmermann (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
The general concept of a Securities Transaction Tax is controversial among academics and politicians. While theoretical research is quite advanced, the empirical guidance in a fragmented market context is still scarce. Possible negative effects for market liquidity and market efficiency are theoretically predicted, but have not been empirically tested yet. In light of the agreement of eleven European member states to implement an STT, this study aims to give a comprehensive overview of the effects of the STT, introduced in France in 2012, on liquidity demand, liquidity supply, volatility and inter-market information transmission. The results show that the STT has led to a decline in liquidity demand, has had a detrimental effect on liquidity supply and negatively influences the inter-market information transmission efficiency. However, no effect on volatility can be observed.
urn:nbn:de:hebis:30:3-335117
Keywords: 330; financial transaction tax; market fragmentation; speculative trading; market quality